Improvement of the Technology of Obtaining Pectin from Local Raw Materials - Norinboev Bakhromjon Ganijonovich; Salokhiddinov Jahongir Saidjon Ogli (Genius Publishing Group, 2023)
Modernization of processing and production in our country, technical re-equipment and production of finished products from raw materials, as well as the production of pectin, as well as filling the domestic market through the widespread introduction of waste-free equipment and innovative technologies, are considered important to be urgent issues of today.
Keywords: Сonfectionery; ready-made pectin; semi-finished product